Curriculum Management and Implementation of Integrative Learning in Islamic-Based Madrasas in Central Java - Sumadi, Eko; Huda, Mualimul (Pascasarjana IAIN Kudus, 2025)
This article aims to explain the curriculum management and implementation of integrative learning in pesantren-based madrasas in Central Java. The research employs a qualitative approach, focusing on two pesantren-based madrasas: MA Al-Azhar in Boyolali and MA Al-Haramain in Jepara. Data were collected through interviews, observations, and documentation. Data analysis techniques include reduction, presentation, and verification or validation of conclusions. The discussion in this article yields the following conclusions: 1) Curriculum management in pesantren-based madrasas involves designing and developing the curriculum according to integrative principles in all areas of learning, integrating religious materials and general materials. 2) Integrative learning is implemented through various teaching methods, the integration of Islamic values into general subjects, and the cultivation of Islamic character in daily life. This is achieved through insertion, complementation, verification, comparison, and project-based learning methods. 3) The success of implementing the integrative curriculum depends heavily on support from various parties, including madrasa heads, teachers, parents, and supportive education policies. Challenges such as limited infrastructure, inconsistent policy implementation, and a lack of resources must be addressed through system improvements, training, and ongoing evaluation. Specific contributions include: 1) Strengthening the concept of integrative curriculum management, 2) integrative learning implementation models, and 3) making practical contributions to educational institutions.